2006
DOI: 10.1029/2006gl028433
|View full text |Cite
|
Sign up to set email alerts
|

Continental deformation in Asia from a combined GPS solution

Abstract: [1] After decades of research on continental tectonics, there is still no consensus on the mode of deformation of continents or on the forces that drive their deformation. In Asia the debate opposes edge-driven block models, requiring a strong lithosphere with strain localized on faults, to buoyancy-driven continuous models, requiring a viscous lithosphere with pervasive strain. Discriminating between these models requires continent-wide estimates of lithospheric strain rates. Previous efforts have relied on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
0
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 34 publications
7
105
0
7
Order By: Relevance
“…[84] Mongolian Altai, northwestern and southeastern parts (NMA and SMA): We rely on GPS results of Calais et al [2006Calais et al [ , 2003 and also England and Molnar's [2005] analysis of them. GPS points are sparse, and these authors have calculated smoothed deformation fields across the Mongolian Altai.…”
Section: à42mentioning
confidence: 99%
See 1 more Smart Citation
“…[84] Mongolian Altai, northwestern and southeastern parts (NMA and SMA): We rely on GPS results of Calais et al [2006Calais et al [ , 2003 and also England and Molnar's [2005] analysis of them. GPS points are sparse, and these authors have calculated smoothed deformation fields across the Mongolian Altai.…”
Section: à42mentioning
confidence: 99%
“…Abundant evidence of strike-slip faulting along the Mongolian Altai accounts for part of the deformation within the belt [e.g., Baljinnyam et al, 1993], but a convergent component also is present. The analyses of Calais et al [2003Calais et al [ , 2006 and England and Molnar [2005] suggest 4 AE 2 mm/yr of shortening.…”
Section: à42mentioning
confidence: 99%
“…Wang et al (2001) identified that the region south of Ganzi-Mani fault moves eastward relative to both Indian and Eurasian plates. Strain rates derived from sparse GPS sites using Delaunay triangle approach are significant at the 95 % and 99 % confidence level in the eastern borderland of Tibetan Plateau (Calais et al 2006). Although crustal deformation in this area has been studied and characterized previously, some unresolved arguments still need to be addressed, e.g., what is the linkage among surficial deformation and stress regime in the crust and mantle deformation?…”
Section: Introductionmentioning
confidence: 99%
“…Как предполагалось ранее [Molnar, Tapponnier, 1975;Tapponnier, Molnar, 1979;Зоненшайн, Савос-тин, 1979;Добрецов и др., 1995], и позже было подтверждено результатами GPS измерений [Yang et al, 2005;Calais et al, 2006;Liu et al, 2007], основным источником геодинамического процесса в рассмат-риваемом регионе является сближение Тарима с Западной Сибирью. Наличие между этими двумя доме-нами слабодеформируемого Джунгарского блока усложняет структуру деформационного пояса с фор-мированием поперечной к направлению сжатия мобильной зоны Тянь-Шаня и диагональной мобильной зоны Алтая.…”
Section: сейсмичность западной части алтае-саянской области джунгариunclassified